"We Blacken Our Teeth with Oko to Make Them Firm": Teeth Blackening in Oceania - Zumbroich, Thomas (Anthropologica, 2015)
Teeth blackening is a form of body modification that was prevalent across parts of Melanesia and Micronesia. The near-permanent colouring of teeth was accomplished by applying plant-based substances combined with a unique kind of ingredient, namely, different soils (asphaltic, peat swamp, volcanic or manganese-containing). Teeth that had been culturally manipulated in a more or less ritualized fashion carried a wide range of associations, embodying local aesthetic criteria and mediating physical and, in particular, sexual maturity and attraction, as well as accomplishing social enhancements that came with maturation. Betel chewing was practised in a very similar region and, though it was distinct, intersected closely with teeth blackening. Subsequent to Western contact, missionary efforts succeeded in repressing teeth blackening effectively, and it disappeared rapidly across the whole area where it was once practised.